Incidence of primary spontaneous pneumothorax: a validated, register-based nationwide study - Olesen, Winnie Hedevang (ERJ Open Res, 2019)
OBJECTIVES: The incidence of primary spontaneous pneumothorax is partly unknown. Commonly quoted estimates were published decades ago and recent large-scale epidemiological publications lack validation. We validated the pneumothorax diagnosis in a national registry and estimated the incidence of primary spontaneous pneumothorax in young patients. METHODS: Complete data on patients with an assigned pneumothorax diagnosis was retrieved from the National Danish Patient Registry. Initially, we validated the diagnosis in a selected population: all patient charts with an assigned pneumothorax diagnosis from one cardiothoracic department over a 25-year period (1984–2008) were reviewed. Subsequently, the national incidence of primary spontaneous pneumothorax in young, healthy individuals was estimated by restricting our population to patients ≤40 years of age admitted during a 5-year period (2009–2014). We performed a systematic read-though of patient charts in 50% of the complete national cohort to ensure that we only included patients with their first episode of primary spontaneous pneumothorax. RESULTS: Validation revealed a poor inter-rater agreement (κ=0.08). Therefore, we abstained from further analysis on directly retrieved data from the national database. Subsequently, a systematic re-evaluation of 7022 patients revealed an incidence rate of 12.3 cases per 100 000 (95% CI 11.5–13.1) in males and 2.2 cases per 100 000 (95% CI 1.9–2.6) in females (male/female ratio 5.9). Compared with the general Danish population, pneumothorax patients had a lower body mass index (p<0.001) and smoked more than the Danish population in general (p<0.001). CONCLUSIONS: The incidence of primary spontaneous pneumothorax in a validated national study was lower than previously reported.